Most Common Symptoms of Prediabetic and Insulin Resistance in Adults in Saudi Arabia - Bukhari, Hassan Mazzhar; Albuqami, Fatoon Mohammed; Asiri, Alanoud Mohammed; Yatim, Ghadeer Othman; Alshareef, Jomana Abdullah; Alzahrani, Ruba Saeed (UI Scholars Hub, 2024)
Background: The prediabetic stage exhibits common symptoms; hence, the risk of developing diabetes can be reduced by identifying these symptoms in the most affected population. This study aimed to examine the prevalence of the main symptoms of insulin resistance in healthy adults aged 18 years and above. Methods: A cross-sectional study was conducted on 1,514 Saudi adults using an online questionnaire collected from 13th November 2020 to 23rd March 2021. Data on personal, lifestyle, and common symptoms were gathered, and the main symptoms were presented as frequencies with percentages. Association with insulin resistance was evaluated using the Chi-square test and other variables by logistic regression models. Results: The four most commonly presented symptoms at a frequency of 23% were tiredness after eating, tiredness all day, frequent urination, and thirst even after drinking. When gender and income levels were considered together with insulin resistance levels in the logistic models, only thirst remained a substantial symptom. Conclusions: In the prediabetic stage, tiredness, urinating more than usual, excessive eating, and thirst were the common symptoms. Implementing public health campaigns and drawing attention to these symptoms for healthcare providers would improve the diagnosis and treatment of diabetes.